Predictors of 2-Year Incidence of Patient-Reported Urinary Incontinence After Post-prostatectomy Radiotherapy: Evidence of Dose and Fractionation Effects - Bresolin, Andrea; Garibaldi, Elisabetta; Faiella, Adriana; Cante, Domenico; Vavassori, Vittorio; Waskiewicz, Justina Magdalena; Girelli, Giuseppe; Avuzzi, Barbara; Villa, Elisa; Magli, Alessandro; Noris Chiorda, Barbara; Munoz, Fernando; et al. (Frontiers in Oncology, 2020)
Objective: To investigate predictors of patient-reported urinary incontinence (PRUI) in the first 2 years after post-prostatectomy radiotherapy (PORT) with particular emphasis on possible dose-effect relationships. Patients and Methods: Two-hundred-thirteen patients, whose clinical and dosimetric data were prospectively collected within a registered multi-institutional cohort study, underwent PORT with adjuvant (n = 106) or salvage (n = 107) intent with conventional (n = 123, prescribed dose to the prostatic bed: 66.6–79.8Gy in 1.8–2.0Gy/fr) or moderately hypo- (n = 90, 65.8–76.8Gy in 2.1–2.7Gy/fr) fractionation during the period 2011–2017. PRUI was evaluated through the ICIQ-SF questionnaire filled in at baseline and every 6 months thereafter. The analysis focused on three ICIQ-based clinically relevant endpoints: (a) very frequent leakage (FREQUENCY, ICIQ3 score >3), (b) moderate to severe amount of urine loss (AMOUNT, ICIQ4>2) (c) objective severe symptoms (OBJECTIVE, ICIQ3+4>5). Predictors of the incidence within 2 years for the three endpoints were investigated focusing only on patients without endpoint symptoms at baseline. A uni-variable logistic regression analysis was performed in order to determine the best dose metrics describing PRUI risk in terms of 2-Gy equivalent dose (EQD2) calculated with different α/β values reported in the literature (0.8, 3, 5Gy), and to identify the most significant clinical variables. Variables showing p < 0.20 at uni-variable analysis were entered into a backward stepwise multi-variable logistic regression analysis. Lastly, the goodness of fit and model calibration were evaluated and internally validated. Results: Patients without symptoms at baseline experienced (a), (b), and/or (c) within 2 years in 41/130 (32%), 40/192 (21%), and 41/129 (32%) of the cases, respectively. EQD2 for α/β = 0.8Gy was the best dose metric associated with PRUI. Multi-variable analysis identified baseline incontinence levels as the strongest predictor for all endpoints (p < 0.006). Both FREQUENCY and OBJECTIVE were significantly influenced also by EQD2(α/β = 0.8Gy). The goodness of fit was excellent, as was the calibration; internal calibration confirmed apparent performance. Conclusion: Baseline mild urinary incontinence symptoms strongly modulate the 2-year risk of PRUI. In addition, FREQUENCY is characterized by a marked dose-effect relationship also influencing the trend of OBJECTIVE, with results more reliable than AMOUNT as an objective index. A strong impact of fractionation on severe PRUI after post-prostatectomy radiotherapy also emerged.